PROBLEMS IN UNDERSTANDING IDIOMATIC EXPRESSIONS BY SENIOR HIGH SCHOOL STUDENTS (RETAIN, 2014)
PROBLEMS IN UNDERSTANDING IDIOMATIC EXPRESSIONS BY SENIOR HIGH SCHOOL STUDENTS Rosyita Okta Utami English Department, Languages and Arts Faculty, State University of Surabaya Rosyitaitak@ymail.com Ahmad Munir English Department, Languages and Arts Faculty, State University of Surabaya Munstkip@yahoo.com Abstrak Idiom berhubungan dengan ungkapan idiomatik yang sebagian besar sering digunakan dalam bahasa sehari-hari. Tapi ironisnya, sebagian besar siswa mengalami kesulitan dalam memahami arti ungkapan-ungkapan idiomatik. Terkait dengan hal tersebut di atas, penulis tertarik untuk mempelajari masalah dalam memahaminya. Peneliti menggunakan penelitian kuantitatif dengan subjek pengamatan siswa kelas XII SMA Negeri 1 Cerme yang meliputi XII Ipa-1, 3 dan 5. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah skor tes dan respon dari kuesioner yang dianalisis menggunakan SPSS. Berdasarkan hasil tes, penulis menemukan bahwa siswa mendapat kesulitan dalam memahami idiom pada jenis verba phrasal dan penggabungan kata kerja. Di sisi lain, konteks mempunyai hasil yang berbeda dalam membantu siswa memprediksi makna ungkapan-ungkapan idiomatic. Ada 3 konteks yang berbeda di dalam tes, dan hasilnya menunjukkan bahwa TMC mempunyai t-value yang lebih tinggi dibandingkan dengan lainnya, itu berarti TMC mempunyai peran yang baik dalam membantu murid-murid dalam mengeksplorasi makna yang ada. Akhirnya, diharapkan bahwa penyelesaian penelitian ini akan berguna untuk guru bahasa Inggris dan peneliti lain. Kata kunci: masalah, ungkapan-ungkapan idiomatik, konteks, siswa SMA. Abstract Idioms which is related to idiomatic expressions have a great extent use in everyday language. But ironically, most students get difficulty in understanding the meaning of idiomatic expressions. Related to the above matters, the writer was interested in studying the problems in understanding it. The researcher used quantitative research in doing her study with the subject of the research third graders of SMA Negeri 1 Cerme which include XII-Ipa 1, 3 and 5. The data collection technique used for this research were test score and questionnaire responses which was analyzed using SPSS. Based on the test result, she found that the students got difficulty in understanding idioms in phrasal verbs and incorporating verbs type. There were three different contexts of the test, and the result showed that TMC has higher t-value which means TMC has a good assistance to help students in exploring the meaning. Furthermore, context has crucial role in determining the meaning which helps and assists students to explore the meaning of idiomatic expressions. Finally, it is expected that the result of this study will be useful for English teachers and other researchers. Keywords: problem, idiomatic expressions, context, Senior High School Students. INTRODUCTION One of the important aspects in English is idiom. Idioms are frequently used in a wide variety of situations. Cooper (1998) states that idioms are so frequently used in spoken and written language that they require special attention in language teaching. ‘An idiom is an expression whose overall figurative meaning cannot be derived from the meaning of its parts’ (Marlies, 1995; p. 283). Moreover, according to Langasher (1968: 79), “an idiom is a kind of complex lexical item. It is a phrase whose meaning cannot be predicted from the meanngs of the morphemes it comprises”. This definitions showed two basic characteristics of the idiom. First, is that idiom is a complex lexical item, second is that meaning cannot be inferred from it parts. In other words, the meaning of the idiomatic expressions is not the sum of the words taken individually. Since idiom is a part of language, it should also be taught along with learning English. In a second language learning classroom, complete idiomatic teaching will not usually be offered and required; however, all learners must be prepared to meet the challenge of idioms which occurs frequently in spoken and written English (Irujo, 1986b). That is why, it is very important for students to master idiomatic expressions. However, the fact showed that idiomatic expressions always cause a lot of problems to learners. According to Cooper (1999), idiomatic expressions understanding study presents a special language problem for all language learners because the figurative meaning is unpredictable. Students usually find the difficulties in recognizing an expression as idiomatic or not, and then understanding its exact meaning. This showed that idiomatic expressions carry a sense that makes the comprehension of an idiom is difficult. In other words, the meaning of an idiom cannot be deduced from the meaning of its constituent parts. The main problem for students is recognizing an idiom and understanding it at once. According to Cooper (1999), “idiom study presents a special language problem for all language learners because the figurative meaning is unpredictable.The result of another study stated that mastering idioms and the ability to use them in the written and the spoken discourse is considered as a sign towards proficiency.” The researcher finds many colleagues who have discussed about problem in understanding idiomatic expressions. The first researcher is Winis (2013) who focused the study on “Investigating the Difficulties Faced in Understanding, and Strategies Used in Processing, English Idioms by the Libyan Students”. The subject of her study was university Libyan students. Then, the second researcher is Meryem (2010) who conducted an observational study entitled “Problems of Idioms in Translation”. From her observation, she thought that students of English really find considerable difficulties in guessing the appropriate meaning of idiomatic expressions. Subjects of her study were children. Those previous studies above proved that students face the difficulties in understanding idiomatic expressions. Those researchers did an observational study to analyze the problem. But the thing that is differentiated here is the subject. So, in this case what makes the two previous studies and this study different is that the researcher uses test and questionnaire for senior high school students. This means that the difference is the subjects that is combination of Indonesian students that makes it more interesting and meaningful. That is why the researcher wants to know further about problem faced by senior high school students in this study. Moreover, it was noticed that there is not much research done in this respect. In the analysis of the students’ performance, in this study the researcher shall be looking for the specific problems students would have in understanding idioms correctly, how the context of the test would assist them in exploring the meaning of idiomatic expressions. For all the above and taking into consideration of the great importance of idiom, the researcher is interested to examine the type of difficulty for senior high school students in understanding the idiomatic expressions. It is accepted that students have different diffculties in different context. It means that they will use their own knowledge which is suitable for them to convey the word meaning. By knowing their problem in understanding idiomatic expressions, hopefully they can solve their problem especially when they face unfamiliar idiomatic expressions in English lessons. From this present study, it is expected that students will be more aware about themselves. Therefore, a study of problems in understanding idiomatic expressions was conducted in SMAN 1 Cerme with the subjects were three classes of third grader. This study is expected to remind teacher about the importance of caring the students’ difficulties through understanding idiomatic expressions and also to give contribution to know about students experience in understanding idiomatic expressions. Hence, this study was intended to find out what kind of idiomatic expressions which is difficult to understand and also to investigate the role of the context in assisting the students to explore the meaning of idiomatic expressions. METHODS The research design of this research was quantitative. The aims of this research was to find the students problem in understanding idiomatic expressions and to know which kind of idiomatic expressions that they do not understand. Moreover, quantitative research emphasizes on numbers, measurements, deductive logic, controls and experiments (McMillan, 1998: 9). The participant of this research are the students of the third grader who study in SMA Negeri 1 Cerme. The researcher chose the third grade based on purposive sampling. The setting of this study was at SMAN 1 Cerme. The school was chosen because of some considerations. First, SMAN 1 Cerme is a good school in Kabupaten Gresik. Thus, the students who are in the third grade are pupils from various Junior High Schools in Gresik with different degree of mastering English lesson and they have been taught English in first and second grade. The researcher only chose three classes include XII-Ipa 1, XII-Ipa 3 and XII-Ipa 5. The student respondents were considered to represent the understanding of idiomatic expressions of Senior High School students in SMA Negeri 1 Cerme. The data of this research was scoring of idiomatic expressions test which was divided into 3 different contexts; Translation Test (TT) with no context, Test-Multiple Choice (TMC) and Test-Blank Filling (TBF). The data was also taken from students’ responses to questionnaire which was divided in 10 statements. The test have been tried out before the researcher conduct the test in school. In that test, they should read the given text and then answer the questions in the form of determining the meaning of 60 idiomatic expressions words. The test contained of some reading passages which contained of 60 numbers of idiomatic expressions target. In doing this research, the researcher did a content validity process which means that the content of the data are valid if it is suitable with the instruments. The result of reliability statistics showed that all values in inter-item correlations are positive, indicate that the items are measuring the same underlying characteristic. The cronbach’s alpha value is .789 which suggests an acceptable internal consistency reliability. Questionaire is used to get students’ viewpoints and experience in understanding idiomatic expressions.However, every statement in the questionaire, ran from: strongly disagree, disagree, I don’t know, agree and strongly agree. Meanwhile, the reasearcher analyzed the test score by seeing the correlation between them using Paired Samples T-Test in SPSS and also analyzed the test score using descriptive statistics. According to Pallant (2010), a paired-samples t-test (also referred to as repeated measures) is used when the researcher has only one group of people (or companies, or machines etc). and collect data from them on two different occasions or under two different conditions. In descriptive statistics, the researcher saw which idioms have the lowest mean from the test score. Moreover, ANOVA was also used to analyze the data to measure the performance of every class. However, the score of the test was used to answer the first, second and third research questions. The result of the questionaire was analyzed using descriptive statistic which showed the mean of every statement from the questionaire to answer research question number three. RESULTS AND DISCUSSION The result shows that many students have difficulties in thedecoding (Non-Identifiable) type of idioms. The findings explained kind of idiomatic expressions which are most difficult to understand and the result data have been ranked from the lowest into the highest mean from the test score. There are 3 points in the first finding. It was found that the lowest mean in Translation Test (TT) score was test number 6 (mean=.14) with idiom “make up”. In other word, idiom of “make up” was type of phrasal verbs idiom. Next point presented that the lowest mean in Test-Multiple Choice (TMC) score was test number 6 (mean=.38) with idiom “make up”. In other word, idiom of “make up” was type of phrasal verbs idiom. Last point showed that the lowest mean in Test-Blank Filling (TBF) score was test number 18 (mean=.07) with idiom “sleep on”. In other word, idiom of “sleep on” was type of phrasal verbs idiom. From the explanation above, it can be concluded that students got phrasal verb idioms as the most difficult type of idioms. However, first finding was related to the type of idioms, each student has different mind in choosing the correct answer of the test. Majority of students get difficulties in answer the idioms in type of phrasal verbs. Makkai (1996: 3) stated that the type of idioms could be classified into lexemic and sememic which includephrasal compounds, incorporating verbs, pseudo-idioms, proverbs and familiar quotations with the most difficulties in phrasal verbs. The next explanation shows different kind of idioms which was stated on the test and also the different types of idioms which was difficult for students to answer it as follows; Lexemic idioms which include phrasal verbs on the test were “make up”, “calls on”, “sleep on”, “give up”, closed up”, “dress up”, catch up”, and “put off”. In the incorporating verbs which was stated on the test were “got away” and “take turns”. Besides that, the type of proverbs is “keep an eye on” and the type of familiar quotation is “in time”. However, half of students in every class got difficulties in answering those types of phrasal verbs idioms. So, the finding was in line with Makkai (1996: 3). Besides that, the researcher also found the role of context to assist the students in exploring the meaning of idiomatic expressions. It can be seen by analyzing it using SPSS in the form of paired samples t-test on Translation Test (TT), Test-Multiple Choice (TMC) and also Test-Blank Filling (TBF). First pair are TT and TMC, there is a statistically significant different in test scores from Translation Test (TT) (M= 61.06, SD= 21.153) with Test- Multiple Choice (TMC) (M= 74.17, SD = 18.876), t (89) = -7.897, p< .0005 (two-tailed). The confidence interval is 95%, ranging from -15.410 to -9.812. The t-value (in this case, -7.89) and the degrees of freedom (df=89), as the Mean difference in the two scores was -13.11, with a 95 per cent confidence interval stretching from a Lower bound of -16.410 to an Upper bound of -9.812. The (p) value is .000, it means that this value is substantially smaller than specified alpha value of .05. Therefore, it can be concluded that there is a significant difference in the Fear of Statistics Test scores. Moreover, in Translation Test with Test-Multiple Choice, the t-value showed (-7.897) which means the score of Test-Multiple Choice is higher than Translation Test. Second pair are TT and TBF, there is a statistically significant different in test scores from Translation Test (TT) (M= 61.06, SD= 21.153) with Test-Blank Filling (TBF) (M= 48.72, SD = 22.418), t (89) = 5.017, p< .0005 (two-tailed). The confidence interval is 95%, ranging from 21.254 to 29.635. The t-value (in this case, 5.01) and the degrees of freedom (df=89), as the Mean difference in the two scores was 12.33, with a 95 per cent confidence interval stretching from a Lower bound of 7.449 to an Upper bound of 17.218. The (p) value is .000, it means that this value is substantially smaller than specified alpha value of .05. Therefore, it can be concluded that there is a significant difference in the Fear of Statistics Test scores. Moreover, in Translation Test with Test-Blank Filling that showed the t-value is (5.017) which means the score of Translation Test is higher than Test-Blank Filling. Third pair are TMC and TBF, there is a statistically significant different in test scores from Test-Multiple Choice (TMC) (M= 48.72, SD= 22.418) with Test-Blank Filling (TBF) (M= 48.72, SD = 22.418), t(89) = 12.064, p<. 0005 (two-tailed). The confidence interval is 95%, ranging from 21.254 to 29.535. The t-value (in this case, 12.06) and the degrees of freedom (df=89), as the Mean difference in the two scores was 25.44, with a 95 per cent confidence interval stretching from a Lower bound of 21.25 to an Upper bound of 29.63. The (p) value is .000, it means that this value is substantially smaller than specified alpha value of .05. Therefore, it can be conclude that there is a significant difference in the Fear of Statistics Test scores. Moreover, in Test-Multiple Choice with Test-Blank Filling showed the t-value is (12.064) which means the score of Test-Multiple Choice is higher than Test-Blank Filling. Based on the all explanation above, it can be conclude that different context has different result, and it made sense that context played a crucial role in understanding idiomatic expressions. As a result, it was same that the skills used to process and understand language in context are thought to be important for the development of idiom understanding (Levorato & Cacciari, 1995). Furthermore, t-value on the test is different in the use of the different types of context. The first pair is Translation Test with Test-Multiple Choice, the t-value showed (-7.897) which means that the score of Test-Multiple Choice is higher than Translation Test. Besides that, the second pair is Translation Test with Test-Blank Filling that showed the t-value is (5.017) which means the score of Translation Test is higher than Test-Blank Filling. Moreover, the last pair is Test-Multiple Choice with Test-Blank Filling that showed the t-value is (12.064) which means the score of Test-Multiple Choice is higher than Test-Blank Filling. It can be conclude that using the context of Test-Multiple Choice (TMC) is the best way in determining the meaning of idiomatic expressions because the t-value is the highest from Translation Test (TT) and Test-Blank Filling (TBF). It can be concluded that TMC is the easier type of test that can be used to predict the meaning of idiomatic expressions. It also means that the context of TMC (Test Multiple Choice) has a good assistance in helping the students to explore the meaning of idiomatic expressions. Furthermore, past research has shown that L2 learners use context to interpret idioms and are more successful to interpret idioms in context than in isolation (Cooper 1998; Ishida 2008b; Liontas 2002). CONCLUSIONS This study is concerned with investigating the problems of understanding idioms from and into English. Two conclusions can be drawn, first result shows that students of senior high school really find considerable difficulties in guessing the appropriate meaning of idiomatic expressions. This is mainly due to the fact that idioms are colorful and has different types in which the meaning is not obvious from the meaning of the constituent words. The type that they get difficult is in phrasal verbs. Second, context has an important role in facilitating the figurative interpretation of idiomatic expressions, and hence, providing correct answers. Because idioms have strong conventional meaning associated, it is possible that context plays much role in helping the students to guess the meaning. At the same time, context plays a crucial role in getting the students to understand the use of an idiomatic expressions. There are 3 different contexts of the test used in this study, and the result shows that the context of TMC (Test-Multiple Choice) is the most successful type of context which assist the students to determine the meaning of idiomatic expressions. TT (Translation Test) and TBF (Test-Blank Filling) have t-value which is under TMC. So, it has been proved that context has crucial role in assisting students to understand the idiomatic expressions. REFERENCES Cooper, Thomas. 1998. Teaching Idioms. Foreign language annals, 31(2), 255-266. Cooper, Thomas. 1999. Processing of Idioms by L2 Learners of English. TESOL Quartsly, 33(2), 233-262. Irujo, S. 1986b. A piece of cake: learning and teaching idioms. ELT Journal, PP.236-237. Langasher, W.R. 1968. Language and Its Structure: Some Fundamental Linguistic Concepts. New York: Harcourt, Brace and World Inc. Levorato, M. C. 1993. The Acquisition of Idioms and the Development of Figurative Competence. In C. Cacciari and P. Tabossi (eds.), Idioms: Processing, Structure, and Interpretation. Hillsdale, NJ: Lawrence Erlbaum Associates, 101-128. Makkai, A. 1996. Idiom Structure in English. The Hague: Mouton. Marlies, E.C. 1995. You Don’t Die Immediately When You Kick an Empty Bucket: A Processing View on Semantic and Syntactic Characteristics of idioms. McMillan, James H. 1992. Educational Research: Fundamentals for the Consumer. Haper Collins Publishers. Meryem, Mezmas. 2010. Problems of Idioms in Translation. Journal of English Language. 7(2), 16-18. Montouri University-Constantie. Pallant, Julie. 2010. SPSS Survival Manual: A Step by Step Guide to Data Analysis Using SPSS (4th edn). Australia: McGraw-Hill. Winis, Noura. 2013. Investigating the Difficulties Faced in understanding, and Strategies Used in Processing, English Idioms by the Libyan Students. International Journal of English Language & Translation Studies vol: 7, Issue: 2, 69-90. University of Sebya, Libyan.